One Year Outcomes Following Transplantation with COVID-19-Positive Donor Hearts: A National Database Cohort Study - Stanley B. Wolfe; Ruby Singh; Dane C. Paneitz; Seyed Alireza Rabi; Chijioke C. Chukwudi; Richa Asija; Eriberto Michel; Asvin M. Ganapathi; Asishana A. Osho (Journal of Cardiovascular Development and Disease, 2024)
The current understanding of the safety of heart transplantation from COVID-19+ donors is uncertain. Preliminary studies suggest that heart transplants from these donors may be feasible. We analyzed 1-year outcomes in COVID-19+ donor heart recipients using 1:3 propensity matching. The OPTN database was queried for adult heart transplant recipients between 1 January 2020 and 30 September 2022. COVID-19+ donors were defined as those who tested positive on NATs or antigen tests within 21 days prior to procurement. Multiorgan transplants, retransplants, donors without COVID-19 testing, and recipients allocated under the old heart allocation system were excluded. A total of 7211 heart transplant recipients met the inclusion criteria, including 316 COVID-19+ donor heart recipients. Further, 290 COVID-19+ donor heart recipients were matched to 870 COVID-19− donor heart recipients. Survival was similar between the groups at 30 days (p = 0.46), 6 months (p = 0.17), and 1 year (p = 0.07). Recipients from COVID-19+ donors in the matched cohort were less likely to experience postoperative acute rejection prior to discharge (p = 0.01). National COVID-19+ donor heart usage varied by region: region 11 transplanted the most COVID-19+ hearts (15.8%), and region 6 transplanted the fewest (3.2%). Our findings indicate that COVID-19+ heart transplantation can be performed with safe early outcomes. Further analyses are needed to determine if long-term outcomes are equivalent between groups.